Development of the EPO-Score – a multivariable tool to predict adverse outcome in infants with perinatal asphyxia undergoing therapeutic hypothermia – a retrospective study - van der Donk, Adriana; Schleier, Maria; Bär, Alisa; Mulzer, Linda; Trollmann, Regina; Schuessler, Stephanie; Hébert, Steven; Hanslik, Gregor; Woelfle, Joachim; Reutter, Heiko; Morhart, Patrick (Frontiers in Pediatrics, 2025)
AimEarly outcome prediction in neonates with perinatal asphyxia receiving therapeutic hypothermia (TH) remains difficult. Although several studies have explored prognostic markers and proposed scoring systems, none of these tools has been adopted for routine bedside use to date. The present retrospective study aimed to design an early prognostic outcome score (EPO-Score). The score serves to identify patients at discharge, predicting severe adverse outcomes according to the Griffiths Mental Development Scales (GMDS) with one year.MethodsPerinatal data was collected from 44 infants with perinatal asphyxia who had received therapeutic hypothermia between 2010 and 2020 at the University Hospital Erlangen, Germany. 27 predictive variables were analyzed regarding their prognostic significance. Analysis showed significant correlations between 15 variables and their outcome. Outcome at one year was classified as favorable (GMDS DQ > 78) or severe adverse (DQ < 78, cerebral palsy, or death). We combined related variables into four indices: systemic injury, neurologic, liver and renal damage. A forward-looking step-by-step analysis revealed a model, explaining 62.1% of the variance in the outcome (R2 = 0.621; p < 0.001). Based on these results, we developed the EPO-Score and correlated the score to the follow-up assessment at one year.ResultsA total of 32 (out of 44) infants met the inclusion criteria. 25 infants experienced a favorable outcome, 7 infants a severe adverse outcome. The EPO-Score integrates eight routine predictors. Average EPO-Score among all infants was 11 points (range 0–24). The EPO-Score showed significant association with the developmental outcome at one year of age (R2 = 0.421, p < 0.001). ROC-analysis demonstrated the EPO-Score's ability to distinguish between favorable and severe adverse developmental outcome, with a cut-off value of 13.5 (AUC = 0.926; 95% CI 0.831–1.00). Infants with a score of 14 or higher were classified as high-risk.ConclusionEPO-Score underlines the correlation between the severity of early multi-organ involvement and severe adverse outcome, demonstrating a high predictive value within our study population. Early identification of patients with severe adverse outcome is important for optimizing neurodevelopmental therapies and providing family support. Nevertheless, external validation is required before the score can be implemented in routine clinical care.